2014
DOI: 10.1007/s00436-014-4056-9
|View full text |Cite
|
Sign up to set email alerts
|

Enolase of Angiostrongylus cantonensis: more likely a structural component?

Abstract: The cloned enolase gene of Angiostrongylus cantonensis (AcEno) comprised 1,667 bp and encoded a peptide with 434 amino acid residues which lacked of a signal peptide but contained a transmembrane region, indicating that AcEno tends to be a structural component (intracellular or membrane protein). The real-time PCR revealed a meaningful difference in the expression level of AcEno in varied development stages. By immunolocalization, native AcEno was detected mainly in the cytoplasm in most tissues, such as parie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“… Ferguson et al (2002) pointed out that enolase played an important role in gene regulation during the proliferation and cleavage of T. gondii . Some studies have found that most of the enolase of Angiostrongylus cantonensis existed in the cytoplasm of the parasite, and it might be involved in regulating the growth and development of the parasite ( Zhang et al, 2014 ). These studies have led us to speculate on the important role of enolase in the growth and development of E. tenella.…”
Section: Discussionmentioning
confidence: 99%
“… Ferguson et al (2002) pointed out that enolase played an important role in gene regulation during the proliferation and cleavage of T. gondii . Some studies have found that most of the enolase of Angiostrongylus cantonensis existed in the cytoplasm of the parasite, and it might be involved in regulating the growth and development of the parasite ( Zhang et al, 2014 ). These studies have led us to speculate on the important role of enolase in the growth and development of E. tenella.…”
Section: Discussionmentioning
confidence: 99%
“…L5 were obtained from the brains of rats infected with 200 L3 15 days previously. Female adult worms were collected as previously described (Zhang et al , 2014). The worms were washed three times with phosphate-buffered saline (PBS; 137 mM NaCl, 2.7 mM KCl, 10 mM Na 2 HPO 4 , 1.8 mM KH 2 PO 4 , pH 7.4) and then stored a −80 °C after soaking in RNAhold reagent (Transgene Biotech, Beijing, China) until RNA extraction.…”
Section: Methodsmentioning
confidence: 99%